Organizational learning and knowledge management - Thong, James Y. L. (2001)
Introduction to the special issue on organizational learning and knowledge management / James Y.L. Thong, Patrick Y.K. Chau, Kar Yan Tam. - A conceptual model for virtual organizational learning / Fu-ren Lin, Sheng-cheng Lin. - Knowledge sharing through intranet-based learning : a case study of an online learning center / Shan L. Pan, Ming-Huei Hsieh, Helen Chen. - Internet diffusion in creative micro-businesses : identifying change agent characteristics as critical success factors / Pascale de Berranger, David Tucker, Laurie Jones